Comparison of Formulas Obtained for Analytical and LQ Idea Approaches to Determine the Optimal Actuator Location in Active Multimodal Beam Vibration Reduction - Elżbieta ŻOŁOPA; Adam BRAŃSKI (Archives of Acoustics, 2014)
In this paper an active general beam vibration reduction via one actuator is considered. The optimal actuator distribution is analyzed with two methods: an exact mathematical principles and the LQ problem idea. It turned out, that the same mathematical expressions are derived. So these methods are equivalent.